3D printing-enabled self-assembling β-nucleating agent alignment: Structural evolution and mechanical performances. (19th April 2022) - Han, Rui; Yang, Qinjie; Wang, Zhongzui; Cao, Dan; Li, Guangzhao; Zheng, Lang; Peng, Biyou; Gao, Xiaoyan; Chen, Gang
Abstract: Achieving good alignment of fillers within the composites is critical towards developing the high performance of the final 3D printed objects. Herein, flow-induced the alignment of self-assembling β-nucleating agent (SANAβ ) within the isotactic polypropylene (iPP) matrix was achieved via fused deposition modeling (FDM) process. The influence of printing speed on the alignment of SANAβ, crystalline structure, and mechanical properties of FDM printed samples were investigated. Due to the converging nozzle effect, SANAβ fibers were fragmented from 26.13 μm to 9.98 μm in length, generating more oriented templates and further preferentially aligned along the printing direction to trigger the iPP crystallization. As a result, the crystal morphology of the printed sample was transformed from α-form to β-form hybrid shish-kebab structure. Highly oriented β-crystal was observed in iPP/SANAβ (FT) samples, as evidenced by 2D-WAXD. 2D-SAXS results revealed the formation of plenty of oriented lamellae in FT samples, which were arranged perpendicular and parallel to the printing direction. The aligned SANAβ also contributed to maintaining a high β-crystal content to overcome the shortcomings of rapid decrease of β-crystal for iPP at a high printing speed. Benefiting from this, with the increasing printing speed, compared with elongation at break of iPP samples decreased from 241.36% to 61.32%, those of FT sample increased dramatically from 305.07% to 390.23% but with a slight fade of less than 1% in the tensile strength. Additionally, the as-printed honeycomb array structure of FT sample presented superior energy absorption capacity and thus could function as loading-bear objects, highlighting the advantages of the alignment of self-reinforcing β-form hybrid shish-kebab. Graphical abstract: Due to the alignment of β-nucleating agent induced by the FDM process, β-form shish-kebab crystals were formed in the printed parts with superior energy absorption capacity but without sacrificing tensile strength. Image 1 Highlights: Self-assembling β-nucleating agent (SANAβ ) was fragmented from 26.13 to 9.98 μm in length during FDM process. More SANAβ were generated, aligned, and functioned as oriented templates to trigger the iPP crystallization. β-form hybrid shish-kebab crystals were formed, where SANAβ was acted as the "shish" and β-lamellae was acted as the "kebab". The aligned SANAβ contributed to maintaining a high β-crystal content even at a high printing speed. The resultant samples presented superior energy absorption capacity without sacrificing tensile strength.